Pharmaceutical study of Triguna and Shadguna Balijarita Makaradhwaja - Dhundi, Shraddha N. (Medknow Publications & Media Pvt Ltd, 2012)
Makaradhwaja is a herbo-minaral drug prepared by Kupipakwa method. In the present study Makaradhwaja was prepared by Triguna and Shadguna Balijarana using Ashtasamskarita Parada. Total five batches of Triguna Makaradhwaja (TM) were prepared by taking 330 g of Kajjali in each batch, average product obtained was 29.12 g. In the preparation of Shadguna Makaradhwaja (SM) too, five batches were prepared, taking 250 g of Kajjali, average product obtained was 16.8 g. The average time taken for flame in TM was 3.01 h and that in SM was 4.58 h. Kupipaka was carried out for 18 and 36 h in TM and SM, respectively. Inductive Coupled Plasma - Optical Emission Spectrometry (ICPOES) revealed the presence of 7.2976 ppm gold in TM, whereas 663.14 ppm in SM.